Cultural and educational environment in the development of younger schoolchildren’s creative potential - Khotinets, Vera Yu.; Shishova, Evgeniya O. (Frontiers in Psychology, 2023)
The purpose of our research is to study the creative potential as psychological capacities for younger schoolchildren’s creative self-realization and self-development in various conditions of the educational environment. The methodological basis of this work is Vygotsky’s conceptual provisions according to which the human psyche is culturally determined, and a sociocultural environment is considered to be the main source and condition for the child’s mental development. The study involved younger schoolchildren (a total of 160 children from the 4th grade aged 9–10 years, n = 160, M = 9.5 years, SD = 2.6; 49% boys) from schools in Kazan (Russian Federation). We used a test of verbal creativity when studying the creative potential of younger schoolchildren, the proposed method is a Russian-language adapted version of the RAT test (remote association test) by Mednik. The Johnson Creativity Inventory was used as adapted by Tunick. To study the level of communicative control, the test “Diagnostics of communicative control” by Schneider was used. To assess the personal qualities of younger students, we used a modified version of the children’s personality questionnaire intended for 8–12 year-old children and developed by Cattell and Koan. As a result of a comprehensive expert assessment, we identified four types of schools with different severity degrees of essential characteristics of educational environments: serene, dogmatic, career and creative. According to the analysis of variance (one-dimensional one-factor ANOVA), the younger schoolchildren’s creative potential was revealed in the context of the educational environment variability and the contingency of the educational environment parameters with the personal characteristics of the children. We have empirically confirmed that in a creative educational environment with cultural content based on ethno-cultural values, patterns and norms, the development of the child is actively supported largely, with the disclosure of his creative potential. Younger schoolchildren are characterized by greater subjective agency and the capability to gain unique achievements in educational and cognitive activity.